2016
DOI: 10.12968/bjom.2016.24.3.203
|View full text |Cite
|
Sign up to set email alerts
|

Can maternity care move beyond risk? Implications for midwifery as a profession

Abstract: Maternal and infant mortality rates are reassuringly low in developed countries. Despite this, birth is increasingly seen as risky by women, health professionals and society in general. In wider society, women are subjected to a litany of risks regarding birth, including sensationalising negative incidents by the media. Within maternity care, both structural and operational factors contribute to heightened risk perceptions. Women are processed through a system where risk-management strategies can take preceden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Pregnancy and childbirth are pertinent examples of the relationship between risk, power and authority. In contemporary MNC, pregnancy and birth are increasingly translated from 'dangerous' to 'risky'from events that are natural and unpredictable to those that can be predicted, controlled, and made safegiving power to those who are the arbiters of, and protectors from, risk (Healy, Humphreys, & Kennedy, 2016a;MacKenzie Bryers & van Teijlingen, 2010).…”
Section: The Jurisdiction Of Midwives In the Netherlands Is Called Inmentioning
confidence: 99%
“…Pregnancy and childbirth are pertinent examples of the relationship between risk, power and authority. In contemporary MNC, pregnancy and birth are increasingly translated from 'dangerous' to 'risky'from events that are natural and unpredictable to those that can be predicted, controlled, and made safegiving power to those who are the arbiters of, and protectors from, risk (Healy, Humphreys, & Kennedy, 2016a;MacKenzie Bryers & van Teijlingen, 2010).…”
Section: The Jurisdiction Of Midwives In the Netherlands Is Called Inmentioning
confidence: 99%
“…The rationale is due to the need to fulfil the role of promoting normal birth, while balancing considerations of risk with the principle of woman-centred care. 32 Clearly, this stance needs to be maintained during discussions relating to 'material risks' in partnership with women. Ultimately, NICE (2016) advocate that pregnant women should be offered evidence-based information and support to enable them to make informed decisions about their care and treatment.…”
Section: Cddft Nhs Foundation Trust Midwife Teacher Teesside Univermentioning
confidence: 99%
“…44 The preference for a home birth is often associated with a natural, non-technical approach to childbirth 28,39,47 and a greater desired level of autonomy, control and responsibility. [48][49][50][51][52][53][54] Women who opt for hospital birth were more often medically oriented and concerned about safety issues. [48][49][50]54,55 However, Coxon et al 10 and Borrelli et al 56 challenge the tendency to see women's choices of birth place as polarised between a preference for a 'natural' or a 'medical' birth as this dichotomy fails to capture the nuances of women's expectations, experiences and the contextual influences.…”
Section: Women's Perspectives On Place Of Birthmentioning
confidence: 99%
“…Women who prefer to give birth outside the hospital are more likely to be older, multiparous and highly educated. 34,48,52,[58][59][60] In a recent Dutch study, women who planned a home birth reported lower levels of pregnancy related anxiety and a depressed mood than women who planned a hospital birth. 61 There are strong indications that pregnancy related anxiety is related to women's risk perception and expectations during pregnancy, at least in nulliparous women.…”
Section: Women's Perspectives On Place Of Birthmentioning
confidence: 99%
See 1 more Smart Citation